Use of air cooling and its effectiveness in dry machining processes - Boswell, Brian (Curtin University, 2008)
Traditional liquid coolants used in metal machining are known to contain chemical carcinogens that could present serious health risks for machine operators and have inherent waste disposal concerns on the environment. In lessening these adverse effects, the manufacturing industry continually seeks to develop machining techniques incorporating liquid-less (dry) methods or environmentally benign coolants. Air-jet cooling is widely regarded as a viable alternative for liquid coolants in machining processes. This thesis proposes a novel air jet cooling arrangement, and assesses its thermal effectiveness and operational compatibility for specific requirements in metal cutting operation. For tests, steel rods were machined on a standard lathe workbench at selected cutting depth, feed and speed. Type 1040 steel, which is commonly used in automobile industry, was chosen as work piece material. Instead of traditional liquid coolant, a specially designed compressed air jet is used to dissipate heat generation in the cutting zone at the tool tip. The tool tip is presented orthogonally to the work piece to maintain conformity with relevant established cutting tool theories. A special air jet configuration based on a Ranque-Hilsch vortex tube was designed and developed for cooling the cutting zone and tool tip. The tool tip temperatures were measured by installing thermocouples at strategic locations on the tool piece and recorded on a data-logger for a range of cutting depths, feeds and speeds. The cutting power was measured with a power meter attached to the electrical power supply to the lathe. For comparison purposes, tests were also conducted with conventional single-nozzle air jets in place of the vortex-tube jets, using traditional liquid coolant and without any cooling applied to the tool tip.A thermal vision camera was also deployed for selected tests to ascertain the temperature characteristics at the tool tip. The data was analysed to establish the thermal characteristics at the tool tip with vortex tube air jet, conventional air jet and no air jet cooling. The measured temperatures and cutting data were used to make assessments on cooling efficiency of jets used and surface finish quality of work piece. Estimates of tool life were made from the cutting theory to determine the effectiveness of the cooling systems used in the machining process. It is found that the proposed vortex tube based air jet cooling arrangement provides a highly efficient heat removal mechanism for metal cutting and delivers thermal cooling performance very much comparable to traditional liquid coolants without the inherent chemical exposure risks to machine operators and harmful impact on the environment. With the proposed air jet cooling, the tool life is very much unchanged and the surface finish quality of work piece shows no significant change while savings will realise though lesser dependency on liquid coolant requiring careful disposal and associated costs.